2021
DOI: 10.3390/w13192631
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Discharge and Reuse Regulation in Costa Rica: An Opportunity for Improvement

Abstract: A database was built with the results of the physicochemical analysis of 23,435 samples of wastewater discharges obtained from the operational reports presented and the cross-checks carried out by the Ministry of Health to the operating entities, in accordance with the provisions of Decree 30661-MINAE-S, for the period 2016–2020. Using Bayesian networks, the probabilities of compliance with current regulations were estimated by preparing an acyclic directed graph for three alternative scenarios. At the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies are specific about the remedies that are most needed to overcome the mishandling of sustainability goals. These are related, for example, to water management in Colombia (Torres et al (2020) [72]), wastewater discharges in Costa Rica (Herrera-Murillo et al (2021) [73]), employee training in Ecuador (Ramírez-Orellana et al (2021) [74]), and producers' certifications in Ghana and Cote d'Ivoire (Ingram et al (2018) [75]). The interest in RSPO and ISPO certification in Malaysia for palm oil producers and the need for government involvement in addressing sustainable production are also reflected in Azis et al (2021) [76] and Majid et al (2021) [77], whereas Nurfatriani et al (2019) [78] strengthened the need for sustainability-related certification in Indonesia (see our results in Table S4, Supplementary Materials).…”
Section: Actions For the Eu's Sustainable Consumption Of Agricultural...mentioning
confidence: 99%
“…Some studies are specific about the remedies that are most needed to overcome the mishandling of sustainability goals. These are related, for example, to water management in Colombia (Torres et al (2020) [72]), wastewater discharges in Costa Rica (Herrera-Murillo et al (2021) [73]), employee training in Ecuador (Ramírez-Orellana et al (2021) [74]), and producers' certifications in Ghana and Cote d'Ivoire (Ingram et al (2018) [75]). The interest in RSPO and ISPO certification in Malaysia for palm oil producers and the need for government involvement in addressing sustainable production are also reflected in Azis et al (2021) [76] and Majid et al (2021) [77], whereas Nurfatriani et al (2019) [78] strengthened the need for sustainability-related certification in Indonesia (see our results in Table S4, Supplementary Materials).…”
Section: Actions For the Eu's Sustainable Consumption Of Agricultural...mentioning
confidence: 99%
“…42 BNs can be applied to a wide range of application domains such as environmental modelling 43 and artificial intelligence, 44 and as mentioned above to quantitative microbial risk assessment (for a review, see Beaudequin et al (2015) 45 ), and water reuse and QMRA. 41,42,[46][47][48] While QMRAs are often constrained by the availability of required data (for example, in dose-response assessments), system models based on BNs are an effective framework that tackle the lack of data. As all data in the network contribute to the whole, accurate predictions can be made with incomplete data or a quite small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that both quantitative (such as water quality and land use data) and qualitative variables (different seasonal scenarios) can be incorporated into a model. Through the design of a Bayesian network, Herrera-Murillo et al [32] estimated the probabilities of complying with regulations in wastewater discharges under some alternative scenarios of operation.…”
Section: Introductionmentioning
confidence: 99%